A case of Fungal Carbuncle in an Immune competent person - Muhammad Umair Butt, Muhammad Almas Murad, Muhammad Afzal, (Pakistan Journal of Medical & Health Sciences, 2022)
Mucormycosis is vessel invading fungal infection and have a very poor prognosis around the globe. It is mostly seen in immunocompromised people but a rare finding can occur in normal people also, however a deep seated cutaneous infection is rare in surgery domain.Multiple types of Mucormycosis have been reported in literature with the cutaneous manifestation being the least common, tissue diagnosis by biopsy followed by antifungals and surgical debridement’s lead to the only treatment modalities available.A carbuncle which basically is a contiguous hair follicle infection that discharges pus from multiple tracts due to abscess underneath the skin.